2008
DOI: 10.1111/j.1601-6343.2007.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term changes in temporomandibular joint function in subjects with cleft lip and palate treated with maxillary distraction osteogenesis

Abstract: To investigate the short-term effects of maxillary distraction osteogenesis (DO) on temporomandibular joint (TMJ) function in 21 subjects with cleft lip and palate (CLP). Design - Morphological changes in the maxillofacial region were measured using lateral cephalometric radiographs taken immediately before (pre-DO) and after DO (post-DO) and 1 year after DO (1-year follow-up). A questionnaire was evaluated using a visual analog scale. A chi-square test was used to compare the prevalence of TMJ symptoms betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
1
1
Order By: Relevance
“…Therefore, the interpretation of this part should be taken with cautions. For EDO, all papers in our study showed increased SN-MP at post-treatment [13][14][15]34,35]. Some papers reported a nonsignificant opening of the mandibular plane angle with the mean change around 18 after distraction [13,34,35].…”
Section: 1contrasting
confidence: 46%
See 1 more Smart Citation
“…Therefore, the interpretation of this part should be taken with cautions. For EDO, all papers in our study showed increased SN-MP at post-treatment [13][14][15]34,35]. Some papers reported a nonsignificant opening of the mandibular plane angle with the mean change around 18 after distraction [13,34,35].…”
Section: 1contrasting
confidence: 46%
“…Twelve papers were finally selected for further quantitative meta-analysis, which could be classified as followed; (1) conventional orthognathic surgery (CO: n = 4) [30][31][32][33], (2) extraoral distraction osteogenesis (EDO: n = 5) [13][14][15]34,35] and (3) intraoral distraction osteogenesis (IDO: n = 3) [17,21,24]. Characteristics of selected studies are presented in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%